Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Pada Perusahaan Manufaktur Periode 2015-2017 - Mega Cristy, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the effect of leverage,firm size,andliquidit on financial performanceat manufacturing company period 2015-2017. The technique used in collecting samples that is purposive sampling, with a sample of 68 companies and 204 company data. Result of research obtained leverage have positive effect to financial performance, firm size have negative effect to financial performance and liquidity have no effect to financial performance